Ceratocone, crosslinking e fatores moduladores da biomecânica da córnea - Torres Netto, Emilio De Almeida [UNIFESP] (2021)
Objectives This thesis aims to present new perspectives involving the corneal biomechanical properties and to optimize the application of corneal crosslinking (CXL) in the treatment of keratoconus (KC). Secondary objectives are: 1. Estimate the prevalence of keratoconus in a pediatric population; 2. Establish mechanical forces that patients with keratoconus apply to their eyelids during the act of eye rubbing; 3. Describe the first association of late keratoconus progression after estrogen regulator therapy; 4. Compare high-order aberrations in keratoconus eyes using the Scheimpflug and double Scheimpflug Placido systems; 5. Assess the biomechanical characteristics of the human cornea and study the role of the Bowman layer with optical coherence elastography; 6. Study whether the Bowman's layer contributes to the biomechanical properties of the cornea clinically; 7. Estimate the biomechanical impact of transepithelial CXL assisted by iontophoresis (I-CXL); 8. Emphasize the importance of CXL modulating factors, especially of transepithelial protocols; 9. Compare functional results of CXL using standard, accelerated treatment and with increased fluency; 10. Develop and evaluate an unprecedented CXL algorithm to treat ultra-thin corneas; 11. Investigate target genes and identify molecular pathways that may be related to biomechanical stability after CXL. Methods The corresponding methodology for each study follows. 1. Prospective, crosssectional, observational and multicenter study, which collected data from pediatric patients from 6 to 21 years of age, using a Scheimpflug rotational corneal tomography system in order to estimate KC prevalence in Saudi Arabia; 2. Fifty-five patients with a clinical and topographic diagnosis of KC were prospectively asked to perform their individual eye rubbing movement on a high-precision scale. The type of rubbing movement and the applied force, represented in newtons (N), were recorded and analyzed. 3. Describe the first case of late keratoconus progression in a 49-year-old woman after the use of tibolone estrogen activity regulator. 4. Keratoconus patients were evaluated sequentially by Scheimpflug and dual Scheimpflug–Placido devices. Differences, correlations, and agreement between values for high order aberrations (HOAs) were analyzed. 5. Human corneal donor buttons were obtained, and Descemet’s membrane and endothelium were removed. In some corneas, Bowman’s layer was ablated by a 20 μm stromal excimer laser ablation. A spectral-domain optical coherence tomography scan was obtained, and displacements were analyzed by optical flow tracking. 6. Human corneas were obtained after endothelial removal for Descemet's membrane endothelial keratoplasty (DMEK). In some corneas, the Bowman layer was removed by a 20 μm excimer laser ablation. A 110 μm thick anterior lamella was obtained and then biomechanical properties were analyzed by twodimensional stress-strain extensometry. 7. One hundred and twelve porcine corneas were divided into 7 groups and analyzed: groups 1, 2 and 3 received standard CXL with epithelial removal (S-CXL) and 30 minutes of irradiation with ultraviolet A (UV-A) at 3mW/cm2, 10 minutes at 9mW/cm2, or were not irradiated (controls). Groups 4, 5, 6 and 7 received I-CXL for 60 minutes at 1.5mW/cm2, 30 minutes at 3mW/cm2, 10 minutes at 9mW/cm2 or were not irradiated (controls). Biomechanical properties were analyzed by one-dimensional stress-strain extensometry. 8. Review and clarification on the estimated efficiency of crosslinking procedures, especially during transepithelial protocols. 9. CXL was performed using three protocols with epithelial removal: Dresden (3mW/cm2 for 30 minutes), accelerated with equivalent total fluence (9mW/cm2 for 10 minutes) and accelerated with increased total fluence (30mW/cm2 for 4 minutes). Efficacy measurements were evaluated 12 months after treatment with Scheimpflug images and included changes in maximum keratometry (Kmax), better corrected distance visual acuity (BCVA), other keratometry, pachymetry, keratoconus indexes, astigmatism, asphericity, refraction and high-order aberrations. 10. 52 eyes with progressive keratoconus and stromal thickness below 400 µm were included. With the ‘sub400’ algorithm developed to treat ultra-thin corneas by adapting fluence individually, corneas were treated without alternative corneal thickening solutions. The study evaluated the efficiency of the new treatment in halting the progression of keratoconus up to 12 months after treatment. 11. Fifteen corneas from eight rabbits were analyzed with corneal transcriptome by cDNA sequencing (RNA-seq) before and after treatment with CXL Results The results are presented in the same order. 1. Five hundred and twenty two patients (1044 eyes) in Saudi Arabia, with a mean age of 16.8 ± 4.2 years, were evaluated. The diagnostic agreement between examiners was 0.81 (almost perfect, according to Cohen kappa coefficient), with a discrepancy in only nine cases. Final KC prevalence of 4.79% (95% CI 2.96 to 6.62) or 1:21 individuals. 2. Three different types of rubbing eyes were detected. Eye rubbing with the fingertip was more frequent (51%), followed by eye rubbing with the knuckle (44%) and with the fingernail (6%). Average applied forces were different: knuckle type eye rubbing applied significantly more force (9.6 ± 6.3N) to the eyelids than with the fingertips (4.3 ± 3.1N) or fingernail (2 , 6 ± 3.3N) (p <0.001 and p = 0.016, respectively). 3. Excessive and late bilateral progression of keratoconus occurred in previously stable eyes in a 49-year-old patient after therapy with selective regulator of tissue estrogenic activity (STEAR). 4. Fifty eyes from 50 patients were evaluated. Trefoil, spherical aberration, and total RMS were significantly different between groups (P < .05). 5. Vertical corneal strain distribution was negative in the anterior and positive in the posterior cornea, indicating simultaneous corneal compression and expansion, respectively. Bowman’s layer caused minor localized differences in corneal strain distribution. 6. No significant differences were observed between the flaps with or without the Bowman layer in the elastic module, neither during preconditioning (874±70 vs 937±106 kPa, p=0.086), nor in destructive tests until rupture (1.03±0.14 vs 1.17±0.14 MPa, p=0.080). 7. In groups I-CXL, only irradiation of 1.5 mW/cm2 for 60 minutes (group 4) showed a significant biomechanical stiffening effect. All S-CXL groups provided a significantly greater effect than I-CXL. 8. In addition to riboflavin and UV-A light, oxygen is the third and fundamental element for crosslinking, and must be taken into account specially in transepithelial procedures. 9. The Dresden Protocol achieved greater changes in the surface variance index (IVS), vertical asymmetry index (IVA), keratoconus index (KI) and regularization index compared to other treatment protocols. There were no other differences between the protocols. 10. New algorithm ‘sub400’ for performing individualized CXL halted keratoconus progression in 90% of the evaluated eyes. No eye showed signs of endothelial decompensation. No significant changes were found for BCVA (p=0.868), sphere (p=0.951) or cylinder (p=0.878). 11. A total of 297 differentially transcribed genes were identified after treatment with CXL. In 9.1% of the significantly different genes, the standard CXL induced a more distinct change in gene transcription than accelerated protocols, which induced a lower biomechanical stiffening effect. Conclusions Finally, here are described the conclusions reached in each of the proposed objectives. 1. The prevalence of KC in the pediatric population in Saudi Arabia is considerably higher than reported in previous studies and in similar studies in other countries; 2. There is great variation in the force exerted on the eyelids, depending on the type of movement when rubbing the eyes. Such data are prerequisites for the development of experimental models of eye rubbing; 3. Patients being treated with STEAR must be monitored closely for changes in the cornea. 4. Significant differences were found between measurements of corneal HOAs generated by Scheimpflug and dual Scheimpflug–Placido devices in patients with keratoconus, and measurements from these devices should not be considered equivalent. 5. Corneal strain distribution are more complex than previously assumed, with a fundamental difference in mechanical response between the anterior and posterior stroma. Clinically, OCE technology might be used to monitor the progression of corneal ectatic diseases and to determine the success of corneal cross-linking. 6. The presence or absence of the Bowman layer did not alter the stiffness of a 110μm corneal lamella. Results may have implications for refractive laser surgery procedures, but also for the new Bowman layer transplantation technique for keratoconus treatment. 7. The biomechanical effect of ICXL increased significantly using low irradiance and long UV-A irradiation. The diffusion of oxygen, therefore, represents a limiting factor, even when the penetration of riboflavin is improved via iontophoresis. 8. Stromal riboflavin concentration is not the only modulating factor in CXL. The epithelium serves not only as a barrier for riboflavin penetration but also as a barrier for oxygen diffusion. Epithelial oxygen consumption is approximately 10 times higher than stromal oxygen consumption; thus, oxygen availability might affect the efficacy of CXL in techniques that are claimed to preserve the epithelium, such as I-CXL. 9. All three protocols showed improvements in Kmax, BCVA and other variables, with similar functional results despite the biggest change in keratoconus indexes after the Dresden protocol. 10. Individualized CXL using the ‘sub400’ protocol halted the progression of keratoconus in ultra-thin corneas in 90% of cases. Although failure rate might be higher than standard CXL, treatment with corneas as thin as 215 µm for the first time is possible. 11. Several target genes have been identified that may be related to biomechanical stability and corneal shape. Understanding the molecular mechanisms after CXL will allow an optimization and individualization of clinical treatment.